2000
DOI: 10.1152/ajpheart.2000.278.4.h1075
|View full text |Cite
|
Sign up to set email alerts
|

Silent α2C-adrenergic receptors enable cold-induced vasoconstriction in cutaneous arteries

Abstract: Cold constricts cutaneous blood vessels by increasing the reactivity of smooth muscle alpha(2)-adrenergic receptors (alpha(2)-ARs). Experiments were performed to determine the role of alpha(2)-AR subtypes (alpha(2A)-, alpha(2B)-, alpha(2C)-ARs) in this response. Stimulation of alpha(1)-ARs by phenylephrine or alpha(2)-ARs by UK-14,304 caused constriction of isolated mouse tail arteries mounted in a pressurized myograph system. Compared with proximal arteries, distal arteries were more responsive to alpha(2)-AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
282
0
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(299 citation statements)
references
References 36 publications
10
282
0
5
Order By: Relevance
“…It was reported that cooling augmented vasoconstriction induced by a2-adrenoceoptor activation and that postjunctional a2-adrenoceptors are important for thermoregulation in this vascular bed (8,9). More recently, it was demonstrated that vasoconstriction induced by the cold was augmented preferentially via a 2C-adrenoceptors, which were silent in a warm environment (10). Taken together, the effects of OPC-28326 shown in this study might be responsible for its a2C-adrenoceptor-blocking action.…”
supporting
confidence: 54%
“…It was reported that cooling augmented vasoconstriction induced by a2-adrenoceoptor activation and that postjunctional a2-adrenoceptors are important for thermoregulation in this vascular bed (8,9). More recently, it was demonstrated that vasoconstriction induced by the cold was augmented preferentially via a 2C-adrenoceptors, which were silent in a warm environment (10). Taken together, the effects of OPC-28326 shown in this study might be responsible for its a2C-adrenoceptor-blocking action.…”
supporting
confidence: 54%
“…With respect to direct local cooling, several lines of evidence point to an involvement of the sympathetic vasoconstrictor system in the reduction of skin blood flow. Postsynaptic ␣ 2 -adrenergic receptors have an enhanced affinity for norepinephrine, perhaps mediated through translocation of ␣ 2C -receptors to the membrane through a Rho kinase mechanism, and there is an increased ␣ 1 -receptor reserve, these effects countering negative effects of cooling on norepinephrine synthesis and release and on contractile function (2,4,6,29,41). Previous studies in our laboratory show that presynaptic blockade of sympathetic vasoconstrictor nerves with bretylium, applied to the intact skin iontophoretically, reverses the initial vasoconstrictor response to local cooling to one of vasodilation (31) and reverses the inhibition by local cooling of reflex cutaneous vasodilation (30).…”
mentioning
confidence: 99%
“…11 ). Neurogenic causes include stress, increased activity of sympathetic nerves, increased number and activation of silent α2 receptors 12 , depletion of neurokinin A, substance P and CGRP (calcitonin gene-related peptide) (ref. 13 ).…”
Section: Discussionmentioning
confidence: 99%